Einlassen, Zulassen, Loslassen: Über ein konstruktives Leidensverständnis - Schnell, Tatjana (DMW - Deutsche Medizinische Wochenschrift, 2019)
Pain or misery strike us – but it is up to us how to deal with them. Suffering is a verb; this underlines the active nature of suffering. The present paper develops a constructive concept of suffering by taking up approaches from existential philosophy and psychology. It suggests that suffering, if allowed and accepted, has the potential to facilitate transformation and, subsequently, to release from pain. The text ends with reflections on how a transformative understanding of suffering can be opened up in the accompaniment of suffering or dying.
Keywords: Schmerz; Leid; Leiden; Existenzphilosophie; Palliative Care